Infrared drones in the construction industry: designing a protocol for building thermography procedures. (October 2017) - Entrop, A.G.; Vasenev, A.
Abstract: While a number of domains readily employ Unmanned Aerial Vehicles with infrared cameras (IR-UAVs), the IR and UAV research directions still need to be bridged in the construction domain. Our research aims to develop a protocol for IR-UAV flights to survey building thermography. Through a series of test flights and a literature study, the protocol was developed. The protocol was verified during a final test flight surveying PV-panels and the thermal shell of a building. By outlining the system, designing a protocol, and reflecting on our experiences, we contribute to the discussion to use IR-UAVs in the construction domain.